Webtoon-based online comics in measuring the Pancasila student profile at Madrasah Tsanawiyah in Riau Province - Mas'ud Zein; Edi Iskandar; Meimunah S. Moenada; Musa Thahir (Institute of Advanced Engineering and Science, 2023)
The objectives of the Pancasila student profile are a number of characters and competencies that are expected to be achieved by students, which are based on the noble values of Pancasila. The purpose of this article is to measure the Pancasila student profile at Madrasah Tsanawiyah (MTs) Riau Province and to find out its effect through the use of webtoon-based online comics. This study conducted a quantitative descriptive approach and focus group discussions in six State MTs. The research instrument used in this study was a Pancasila student profile questionnaire, which was distributed to students. The findings show the six indicators and their implementation in each madrasa. The six MTs in this study were categorized as very good, which indicated the need to increase Pancasila student profile. There are considerable disparities in indices of religion, fear of God Almighty, and noble character, global variety, mutual collaboration, independence, critical thinking, and creativity for Pancasila student profile policies. The use of webtoon-based online comics in measuring the Pancasila student profile studied in this study is based on madrasa policy and it has not been thoroughly tested in all MTs in Riau Province. Furthermore, it can consider its use in a wider Madrasah Tsanawiyah frame. MTs in Indonesia can measure the Pancasila student profile through the use of webtoon-based online comics to achieve student character standards that are in line with educational goals in Indonesia. This research provides a webtoon-based online comic framework to measure the Pancasila student profile.